THE INFLUENCE OF ELDERLY EXERCISE ON THE PHYSICAL HEALTH OF THE ELDERLY IN CANDIMULYO VILLAGE, JOMBANG REGENCY - Hidayah, Ardiyanti; Anggraini, Rista Dian; Farida, Siti Nur (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2024)
Background: Physical health is anything related to the physical. There are many things you can do to improve physical health, such as exercise (physical activity), meeting nutritional needs, and mental health. Objective: This research aimed to determine the effect of elderly exercise on the physical health of elderly people in Candimulyo Village, Jombang Regency. Method: This type of research is an experiment with a one group pre-posttest design. with a sample of 15 people or total sampling, the level of physical health was measured by measuring resting and exercise pulses. The statistical test used in this research is the t-test. Results: Based on the results of research and hypothesis testing carried out by researchers, the results of the pre-test and post-test resting pulse t-test were t-count 80.769 while t-table 1.761 (t-count 80.769 > t-table 1.761) with a significant level of α = 0.05 and the results of the pulse t-test The pre-test and post-test exercises were t-count 23.469 while t-table 1.761 (t-count 23.469 > t-table 1.761) with a significant level of α = 0.05. Conclusion: It can be concluded that "There is a significant influence of elderly exercise on the physical health of the elderly in Candimulyo Village, Jombang Regency”.